Influence of Different Polishing Systems on Surface Roughness and Microhardness of Bulk-fill Resin-based Composites: An In Vitro Study - Siti H Omar; Muhammad S Alauddin; Laila A Hassan; Faizah A Fatah (Jaypee Brothers Medical Publishers (P) Ltd, 2025)
Indexed by Scopus